2014
DOI: 10.1016/j.indmarman.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Relational key account management: Building key account management effectiveness through structural reformations and relationship management skills

Abstract: Business School. His research interests include services marketing, internal marketing, digital marketing, key account management and business-to-business marketing. His work has been published in many American and European prestigious journals Nektarios Tzempelikos is Senior Lecturer in marketing in the Lord Ashcroft International Business School, Anglia Ruskin University. His research interests include key account management, relationship marketing and customer value in the business-to-business context. His … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 92 publications
1
27
0
1
Order By: Relevance
“…Further, a recent study found that relationship quality consisted of customer satisfaction, service quality influence, customers' repurchase intentions, and subjective well-being [11]. The study suggests that relationship quality is a central issue for long-term success in management and business relationships [12]. Relationship quality is the factor that enhances profitability for both parties [13].…”
Section: Relationship Qualitymentioning
confidence: 98%
“…Further, a recent study found that relationship quality consisted of customer satisfaction, service quality influence, customers' repurchase intentions, and subjective well-being [11]. The study suggests that relationship quality is a central issue for long-term success in management and business relationships [12]. Relationship quality is the factor that enhances profitability for both parties [13].…”
Section: Relationship Qualitymentioning
confidence: 98%
“…This study's contributions are not limited, however, to the field of academia. As key account management can be a significant basis for developing a competitive advantage (Gounaris and Tzempelikos 2014), present study model on key account management and subsequent empirical results have strong implications for managers and for strategists. This paper provides a set of tools for scanning the important influencing variables that can help managers to visualize their impact on their capacity that is fundamental for showing greater performance in the field of key account management.…”
Section: Resultsmentioning
confidence: 92%
“…Bangladesh is now in the second position with an export volume of 28 billion worth of garments in the world apparel market (Breed 2012;BGMEA 2016). The country's overseas sales of apparels grew by 10.21 percent of the fiscal year 2015-2016 compared to the fiscal year 2014(BG-MEA 2016. Besides the success stories, today these garments manufacturers and exporters are facing numerous challenges (Haider 2007;Nuruzzaman and Haque 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Atanasova and Senn, 2011; Davies and Ryals, 2009;Davies and Ryals, 2013;Gounaris and Tzempelikos, 2014;Guenzi et al, 2007;Pardo et al, 2014;and Sharma, 2006. To check the cross-functionality of the KA teams; the training provided to these teams; the job enlargement possibilities; the team performance; the teams' profile and skills; and the team proactivity, communication and conflict resolution skills. Atanasova and Senn, 2011;Baddar Al-Husan and Brennan, 2009;Guenzi and Storbacka, 2015;Kotter and Schlesinger, 2008;Marcos-Cuevas et al, 2014;Gebauer et al, 2013;Steward et al, 2010;Stock, 2006;Storbacka, 2012;Tzempelikos and Gounaris, 2015; To check the profile and skills of the team members to perform their action (which includes attention to the proactivity, communication and conflict resolution skills); to check the skills to develop innovative solutions; to improve the competitive advantage in rough moments, or to introduce new ways of doing business.…”
Section: What To Do Regarding Managers and Teams Referencesmentioning
confidence: 99%